The current role of BTK inhibitors in the treatment of Waldenstrom's Macroglobulinemia. Issue 8 (2nd August 2020) - Gavriatopoulou, Maria; Fotiou, Despina; Ntanasis-Stathopoulos, Ioannis; Dimopoulos, Meletios Athanasios
ABSTRACT: Introduction: Waldenstrom's Macroglobulinemia (WM) is a rare, indolent lymphoplasmacytic lymphoma characterized by heterogeneous clinical and genomic profile. Bruton's tyrosine kinase (BTK) is central to the signaling pathways required for clonal WM cell survival, and BTK inhibitors currently have an imperative role in the treatment of WM. Areas covered: The central role of BTK in WM will be described, and the rationale behind the development of BTKi. Clinical trial data that led to the approval of ibrutinib (the first-in-class BTKi) will be reviewed. Despite its potency and safe toxicity profile, ibrutinib does not induce deep remissions, and responses are mutational-status dependent. The mechanisms that lead to resistance to this agent are being investigated. Ibrutinib treatment has to be continuous; consequently, patients face the effects of long-term toxicity. In that context, second-generation inhibitors are in clinical development with fewer off-target effects and an efficacy profile, which will be determined based on long-term follow-up data. Expert opinion: The optimal therapeutic approach for WM patients remains to be established. The question of whether a combinatory (or synergistic) regimen to overcome resistance and allow for a fixed treatment duration will allow for deep and durable response is being addressed in ongoing clinical trials.